Levantamento epidemiológico na cidade de Maringá : disfunção temporomandibular e dor orofacial e suas variáveis - Progiante, Patricia Saram (2012)
To carry out an epidemiological survey of Temporomandibular Disorders and Orofacial Pain (TMD and OFP) and correlate it with sleep and psicossocial variables in the City of Maringá, State of Paraná, Brazil. The Axes I (questions 0 to 7) and II of the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) and the Sleep Assessment Questionnaire (SAQ) were used for pain, sleep, depression and somatization assessment. The population were 1775 individuals, both sexes, between 20 and 65 years of age, users of the Brazilian Public Health System (SUS). The data analysis was performed with STATA 11.0, and the Pearson s Chi Square test and Linear Regression were used for correlations assessment (p < 0.05). The final sample (N = 1,643) was comprised predominantly by men (67.7%), between 20 and 39 years of age, married (48.4%), caucasian (70%), with an average montlhly income between US$ 250.00 and US$ 1,500,00, and with high school education (31%). The Chronic Pain Grade (CPG) Classification demonstrated that the majority of our population had no pain (63.8%) or low intensity pain (18.4%) with low disability (Grades 0 and I); however, 12.7% of the population had high pain intensity with low disability (Grade II), and 5.1% had high TMD pain disability (Grades III and IV). The need for absence leave due to pain was for very short periods of time (1 to 2 days) in 13.8% of the population. A low global score for sleep, depression and somatization with and without pain, and a positive low correlation of Characteristic Pain Intensity (CPI) with these psychossocial variables was found. An important part of the Brazilian population presented the need for TMD and OFP multidisciplinary treatment (17.8%) and this should be considered in future public health policies